LEVEL REGARDING CORRUPTION OF LOCAL GOVERNMENTS: PERSPECTIVE OF FINANCIAL STATEMENT ACCOUNTABILITY, FINANCIAL PERFORMANCE, AND SIZE OF LOCAL GOVERNMENTS - Kumalasari, Roro Endah (Jurnal Ekonomi, Bisnis & Entrepreneurship (e-Journal), 2020)
This study intends to determine the magnitude of the influence of regional financial statement accountability, local government financial performance, and local government’s size on local governments’ corruption in the Province of Indonesia. This study uses a quantitative approach using secondary data obtained from the Regional Government Financial Statements for 2011 to 2015 and the amount of corruption reported by the KPK from 2011 to 2015. Using panel data to analyze research data to obtain the best model is the Random Effect. The results showed that the accountability of local government financial reports, local government financial performance, and local government size simultaneously had a significant effect on corruption.